Medication risk checklist for older adults (LOTTA) - development and validation of a self-assessment tool - Dimitrow, Maarit; Saarenmaa, Roosa; Airaksinen, Marja; Hassan, Ghada; Puumalainen, Emmi; Pitrová, Markéta; Kivelä, Sirkka-Liisa; Fialová, Daniela; Puustinen, Juha; Toivo, Terhi (Annals of medicine, 2023)
BACKGROUND: Patient safety strategies highlight patients' own active involvement in ensuring medication safety. A prerequisite for involving patients in their medication therapy is having tools that can assist them in ensuring safe medicine use. Older home-dwelling adults with multiple medications are at high risk for medication-related problems, yet only a few age-specific patient self-administered medication risk screening tools exist. This study aimed to develop, validate, and assess the feasibility of a self-administered medication risk checklist for home-dwelling older adults ≥65 years. MATERIALS AND METHODS: The draft checklist was formed based on a validated practical nurse-administered Drug Related Problem Risk Assessment Tool supplemented with findings from two systematic literature reviews. The content validity of the draft checklist was determined by a three-round Delphi survey with a panel of 19 experts in geriatric care and pharmacotherapy. An agreement of ≥80% was required. A feasibility assessment (i.e. understandability of the items, fill-out time of the checklist) of the content-validated checklist was conducted among older adults ≥65 years (n = 87) visiting community pharmacies (n = 4). Data were analysed using qualitative content analysis. RESULTS: The final validated and feasibility-tested Medication Risk Checklist (LOTTA) for home-dwelling older adults consists of eight items screening the highest priority systemic risks (three items), potentially drug-induced symptoms (one item), adherence, and self-management problems (four items). The checklist proved feasible for self-administration, the mean fill-out time being 6.1 min. CONCLUSIONS: A wide range of potential medication risks related to the medication use process can be identified by patient self-assessment. Screening tools such as LOTTA can enhance early detection of potential medication risks and risk communication between older adults and their healthcare providers. A wider and more integrated use of the checklist could be facilitated by making it electronically available as part of the patient information systems.
Keywords: kontrolní seznam; senioři; zdravotnický personál; Patient Safety; self-management; risk screening; Humans; patient safety; Health Personnel; primary care; Aged; Self-Assessment; Checklist; sebezhodnocení (psychologie); Medication therapy; lidé; bezpečnost pacientů; older adults